Contemporary use of co-design and computational design methods for inclusive built environments: a case study of platform-train interfaces - Kapsalis, Efthymios Timo (2024)
Accessibility of the built environment has a huge impact on the experience and extent of disability. This is particularly true for public spaces – for example, train stations – both indoors and outdoors. Mobility-related impairments are amongst the most common types of impairments, according to international disability indexes. There is an emerging need for researchers and practitioners to investigate the built environment through the lens of users of mobility assistive devices (MobAD) – such as wheelchairs or canes. The profound implications of design decisions on societal equality and individual wellbeing underscore the significance of this research.